The impact of the Vision 2030 projects on contemporary architecture: Analytical study of Saudi architecture map - Osman, Nazar Mohamed Elkheir Mohamed (Journal of engineering sciences and information technology, 2025)
This study aims to explore the impact of the Saudi Vision 2030 projects on contemporary architecture and to demonstrate the importance of contemporary architecture in preserving national identity. Its significance stems from the Kingdom of Saudi Arabia's Vision 2030, launched by His Royal Highness Prince Mohammed bin Salman, which has had a clear impact on improving the quality of contemporary architecture through large projects such as the Public Investment Fund projects, NEOM, the Red Sea projects, and the tourism sector. These contribute to creating innovative designs that enhance the quality of innovation and strengthen national identity by integrating national heritage, resulting in an urban scene with specifications and contemporary Saudi architectural designs. In this research, we present an analytical study of the map of Saudi architecture, illustrating how the Kingdom of Saudi Arabia combines contemporary and traditional architecture under Vision 2030 and how the projects of this vision contribute to the future of contemporary architecture. I relied on a questionnaire as a data collection tool, distributing it to citizens in areas where the map of Saudi architecture was implemented, with a sample size of 150 citizens, of which 82% were male and 18% female. The statement regarding the impact of the Kingdom's Vision projects on architecture received a high percentage, followed by Saudi architecture map.
Keywords: Impact of Projects; Vision 2030 of the Kingdom; Contemporary Architecture; Map of Saudi Architecture